2008
DOI: 10.1128/cmr.00014-08
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Biosafety: a Review of the Principles and Effectiveness of Microbiological Containment Measures

Abstract: SUMMARY We examined the available evidence on the effectiveness of measures aimed at protecting humans and the environment against the risks of working with genetically modified microorganisms (GMOs) and with non-GMO pathogenic microorganisms. A few principles and methods underlie the current biosafety practice: risk assessment, biological containment, concentration and enclosure, exposure minimization, physical containment, and hazard minimization. Many of the current practices are based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 130 publications
1
52
0
14
Order By: Relevance
“…Outro ponto a ser considerado é que os laboratórios de campo comumente apresentam características improvisadas, proporcionando menor condição de controle de riscos 52,77 . Assim, observa-se que existem diversos fatores, próprios da estrutura de trabalho nas pesquisas de campo, que determinam riscos de diversas naturezas, os quais podem afetar o indivíduo e representar, isoladamente ou em conjunto com outros riscos, uma condição para o adoecimento.…”
Section: A Estrutura Do Trabalho De Campo E a Caracterização De Outrounclassified
“…Outro ponto a ser considerado é que os laboratórios de campo comumente apresentam características improvisadas, proporcionando menor condição de controle de riscos 52,77 . Assim, observa-se que existem diversos fatores, próprios da estrutura de trabalho nas pesquisas de campo, que determinam riscos de diversas naturezas, os quais podem afetar o indivíduo e representar, isoladamente ou em conjunto com outros riscos, uma condição para o adoecimento.…”
Section: A Estrutura Do Trabalho De Campo E a Caracterização De Outrounclassified
“…Risk groups are a way of categorizing the level of risk associated with a particular biological agent 39 . Risk groups range from lower • An individual human to another human or to an animal; or • An individual animal to another animal or to a human; and  In respect of which effective treatment and preventive measures are not usually available.…”
Section: Coccidioidomycosis Is Generally Caused Bymentioning
confidence: 99%
“…However, these regulations cannot cover all aspects of working with new organisms. The severe acute respiratory syndrome (SARS) coronavirus outbreak in 2003 can be seen as a showcase for this dilemma 4 . The notion that scientists who work in BSL-3/4 laboratories cannot be trusted seems contradictory to the fact that these scientists, working with highly contagious and pathogenic agents, have an eminent interest in their own health and safety.…”
mentioning
confidence: 99%
“…A recent literature review concluded that deviation from general 'good microbiological practice' is the most frequent cause of laboratory-acquired infections and that training for compliance with procedures and regulations seems to be the best method to avoid such infections 4 . In this light, our course offers the opportunity to improve the basic training that is available for BSL-3/4 scientists and the prerequisite initial training for beginners.…”
mentioning
confidence: 99%